The Potential for a Sovereign Wealth Fund to Acquire and Exert Influence Over the Eurozone - Thomas Junghanns; Jan Körnert (Intereconomics, 2022)
The financial clout of the world's sovereign wealth funds (SWFs) is massive, and many of these are controlled by authoritarian regimes. It cannot be ruled out that these funds might acquire shareholdings in banks that play key roles in other countries. This paper studies the extent to which SWFs have the potential to use shareholdings in critical banks as mechanisms to exert influence on other countries' banking, economic and political systems. We identify banks holding critical positions within the eurozone countries that might be exploited in the pursuit of power and determine whether SWFs could acquire simple or qualified majorities in these banks and whether they would have sufficient assets to enter into such investments. The paper concludes that three authoritarian regimes – China, Abu Dhabi and Saudi Arabia – each have a SWF which would need to invest not even half of its assets to acquire such sweeping influence.
Keywords: F63; F64; N10; 330